1994
DOI: 10.1007/bf00008341
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of exogenous 2′-14C-indole-3-acetic acid and 3′-14C-tryptophan exposed to the roots of three wheat varieties

Abstract: This study was conducted to determine if plants can assimilate indole-3-acetic acid (IAA) from rooting media and if exogenous L-tryptophan (L-TRP) can be assimilated and converted by plants into auxins. The addition of 2'-laC-IAA (3.7 kBq plant -s) to wheat (Triticum aestivum L.) seedlings of three varieties grown in nutrient solution resulted in the uptake (avg. = 7.6%) of labelled IAA. Most of the label IAA was recovered in the shoot (avg. = 7.2%) with little accumulation in the root (avg. = 0.43%). A portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…It is now well established that various Azotobacter species are capable of synthesizing plant hormones and is considered the most plausible mechanism of action. Significant yield increase in response to L-TRP application in present study is in agreement with the findings of many other workers (Martens and Frankenberger, 1994;Arshad et al, 1995). The increased N concentration and uptake in grain and straw in our study is also in accordance with the findings of many other workers (Arshad et al, 1994a,b;Zahir et al, 1997).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is now well established that various Azotobacter species are capable of synthesizing plant hormones and is considered the most plausible mechanism of action. Significant yield increase in response to L-TRP application in present study is in agreement with the findings of many other workers (Martens and Frankenberger, 1994;Arshad et al, 1995). The increased N concentration and uptake in grain and straw in our study is also in accordance with the findings of many other workers (Arshad et al, 1994a,b;Zahir et al, 1997).…”
Section: Discussionsupporting
confidence: 94%
“…The effect of L-TRP on growth and yield of wheat could be attributed to either auxin metabolites produced by the rhizosphere microflora which were subsequently taken up by plant roots or direct uptake of L-TRP by the plant roots with subsequent catabolism into auxins within the plant tissue and/or alteration in the balance of the rhizosphere microbial community in response to L-TRP addition which may affect growth and yield of wheat. However, Martens and Frankenberger (1994) reported very poor uptake of labelled L-TRP compared with labelled IAA by wheat seedling roots. They also demonstrated poor endogenous conversion of exogenously applied labelled tryptophan into auxins by wheat seedlings grown under axenic environments.…”
Section: Discussionmentioning
confidence: 95%
“…In this research we showed that bacterial IAA stimulates the development of the host plant root system. The advantage for root-associated bacteria is a rich supply of nutrients, as much of the metabolic products of the carbon fixed by plants is lost from roots and moves into the rhizosphere as exudates, lysates, and mucilage (32).…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan (Trp) serves as a physiological precursor for the biosynthesis of auxin in higher plants and in microbes (Frankenberger and Arshad 1995). Root exudates are natural sources of Trp for the rhizosphere microflora, which may enhance auxin biosynthesis in the rhizosphere (Martens and Frankenberger 1994). The most efficient auxin producers are found among fungal inhabitants of the plant rhizosphere and phyllosphere (Tsavkelova et al 2005).…”
mentioning
confidence: 99%